PENGARUH PEMBERIAN EKSTRAK UBI UNGU (IPOMEAE BATATAS L) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL PADA SERUM TIKUS WISTAR (RATTUS NOVERGICUS) YANG DIBERI INDUKSI KUNING TELUR PUYUH - LUFTHY DWI PUTRA HUTAGALUNG; IRFAN HAMDANI (LP2MTBM MAKARIOZ, 2020)
Hypercholesterolemia and oxidative stress are still a health problem to date because they are associated with theemergence of cardiovascular disorders with various complications. Indonesian people have utilized many types of plants thatcan be used as alternatives to support health. In several studies, several plants have been found that can reduce bloodcholesterol levels, one of which is purple yam (Ipomea batatas). To find out how the effect of purple sweet potato fruit extract(Ipomea batatas) can reduce total cholesterol levels in wistar rats that experience dyslipidemia. This study was a Trueexperimental study, with the research design used was the Post Test Only Control Group Design. Research The results ofthis study use. Annova test analysis obtained the value of P Value as indicated by the value of Asymp. Sig is 0.005 whichmeans that there is an effect of purple sweet potato fruit extract (Ipomea batatas l) can reduce total cholesterol levels inwistar rats that have dyslipidemia. There is a correlation between the effect of purple sweet potato fruit extract (Ipomeabatatas l) against decline total cholesterol levels in wistar rats that experience dyslipidemia.